Metinlere yönelik okuma motivasyonu ölçeği: Geçerlik ve güvenirlik çalışması - AYDEMİR, ZEYNEP (My University, 2013)
In this study, it was aimed to develop a reading motivation scale in order to determine reading motivations of students for texts. The work group was consisted of 259 students who were attending to 5th grade of the schools in the center of Sakarya during the 2nd term of 2010-2011 school year. First of all, in the process of developing the scale, a review of literature was made and a pool of 60 items was created. Opinions of experts were applied for the content validity and exploratory factor analysis was conducted for the construct validity of the scale. Finally, internal consistency coefficient was applied for the reliability studies. When the results were assessed, a valid and reliable scale that consists of 22 items and four factors which are \"perceived reading difficulty,\" \"reading ability,\" \"effort/being appreciated to read\" and \"social aspect of reading\" was obtained. The four factors found in the scale explained %46.23 of the total variance. In total, internal consistency coefficient was found as.81. These values show that the scale explained the reading motivations of the primary school students of the 5th grade for texts in a valid and reliable manner.

Bu çalışmada ilköğretim öğrencilerinin metinlere yönelik okuma motivasyonlarını belirlemek üzere okuma motivasyonu ölçeği geliştirmek amaçlanmıştır. Çalışma grubunu 2010-2011 öğretim yılı II. Dönem Sakarya ili merkezinde bulunan okullardaki 259 5.sınıf öğrencisi oluşturmaktadır. Ölçek geliştirme sürecinde ilk olarak alan yazın taraması yapılmış ve 60 maddelik bir havuz oluşturulmuştur. Ölçeğin geçerlik çalışmalarında kapsam geçerliği için uzman görüşü alınmış, yapı geçerliliği içinde açımlayıcı faktör analizi yapılmıştır. Son olarak da güvenirlik çalışmaları için iç tutarlılık katsayısı hesaplanmıştır. Sonuçlar değerlendirildiğinde, “okuma zorluğunun algılanması” , “okuma yeterliği”, “okumaya yönelik çaba/takdir edilme” ve “okumanın sosyal yönü” olmak üzere dört faktör ve 22 maddeden oluşan geçerli ve güvenilir bir ölçek elde edilmiştir. Ölçekte yer alan dört faktör toplam varyansın %46.23’ünü açıklamaktadır. Toplamda iç tutarlık katsayısı da .81 olarak bulunmuştur. Bu değerler ölçeğin ilköğretim 5. sınıf düzeyinde öğrencilerin metinlere yönelik okuma motivasyonlarını iyi bir şekilde açıkladığını göstermektedir.
Reading motivation scale for texts: A validity and reliability study
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Reading; Reading motivation; Reliability; Scale development; Text; Validity; Reading; Text; Reading Motivation; Scale Development; Validity; Reliabilit; Okuma; Metin; Okuma Motivasyonu; Ölçek Geliştirme; Geçerlik; Güvenirlik